PENINGKATAN KEMAMPUAN PENALARAN FORMAL SISWA MELALUI PENERAPAN MODEL LEARNING CYCLE 5E DALAM PEMBELAJARAN IPA FISIKA KELAS VIII MTsN SUNGAI TONANG - Rosmayanti Rosmayanti; Zulhelmi Zulhelmi; Muhammad Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to determine the increase student’s ability of the reasoning formal with Lerning Cycle 5E model and conventional through the science physics learning class VIII MTsN Sungai Tonang. Population of this research is class VIII consisting of 2 class. Sample taken is 2 class. Techniques determining the experiment’s class and control’s class with Simple Random Sampling. This research was conducted in MTsN Sungai Tonang precisely in July until December 2015. The design of this research was a Quasi Experimental Design with Nonequivalent Control Group Design. Data collection Instruments in this research was the test learning outcomes the ability of reasoning formal given before and after learning. Data were analyzed using descriptive analysis and inferential. The result analiysis descriptif showed absorpsion that after learning implementation of the learning cycle 5E model is 74.4% category of good. The result inferential obtained significant value 0.00 (0.00 < 0.05) then Ha accepted, so it can be concluded that significant different against the student’s reasoning formal the science physics learning class VIII MTsN Sungai Tonang the application of Learning Cycle 5E model with class the application conventional learning. So effective to improve the ability reasoning formal .Key Words: Reasoning Formal, Learning Cycle 5E, Force and Acceleration